항공기용 외부연료탱크의 구조 건전성 검증을 위한 구조 정적시험 - 김현기(Hyun-gi Kim); 김성찬(Sungchan Kim); 안수홍(Su-hong An); 하병근(Byoung-geon Ha) (항공우주시스템공학회지, 2023)
Aircraft components can only be mounted on an aircraft if they have been proven to have structural soundness under flight load conditions. Among main components of the aircraft, external fuel tank is a component that extends the range of an aircraft. It should be able to be separated from the aircraft in emergency situations. This study presents results of structural static test performed to verify the structural soundness of an external fuel tank for aircraft under all loading conditions. In the main text, a structural test set-up diagram consisting of test fixture, hydraulic supply unit, load control system, data acquisition system, and pressure supply device is presented. Test profile for each test load condition is provided. As a result of the structural static test, it was found that the load applying device was properly controlled within the allowable range of error between load input value and load output values during test with internal pressure of test specimen maintained well without leakage. In addition, it was confirmed that no damage or buckling causing serious structural defects in the specimen under the required load condition occurred. In conclusion, the developed external fuel tank has sufficient static strength under the required load condition. 항공기에 장착되는 구성품은 항공기 운용 조건에서 구조 건전성이 입증되어야 한다. 항공기 주요 구성품 중에서 외부연료탱크는 항공기의 항속거리를 증가시키는 역할을 하는 구성품으로써 비상상황에서는 분리할 수 있는 기능도 요구된다. 본 연구에서는 항공기 비행하중조건에 대해 항공기용 외부 연료탱크의 구조 건전성을 검증하기 위해 수행한 구조 정적시험 결과를 제시하였다. 본문에서는 외부연료탱크 구조 정적시험에 사용되는 시험치구, 유압장치, 하중제어 시스템, 데이터 획득장비 그리고 압력 공급장치로 구성되는 시험구성도를 제시하고, 각 시험하중조건에 대한 시험 프로파일을 제공하였다. 구조 정적시험 결과, 시험이 수행되는 동안 하중 인가값과 출력값 사이의 오차가 허용범위 내에서 하중 인가장치가 적절히 제어되었고 시험체의 내부압력도 누설없이 잘 유지되는 것으로 파악되었다. 또한, 요구 하중조건하에서 시험체에 심각한 구조적 결함을 일으키는 손상이나 좌굴이 발생하지 않는 것으로 확인되었다. 결론적으로, 본 연구에서 다루고 있는 항공기용 외부연료탱크는 요구된 하중조건에 대해 충분한 구조 건전성을 가지고 있음이 입증되었다.